(untitled) - Naidu, Prabhakar S. (Oxford, 2006)
This text covers Digital Signal Processing (DSP) including signals and systems, discrete fourier transformers, digital filters, adaptive filters and beam forming.
Keywords: Signal processing,Thiết kế tín hiệu; Digital techniques,kỹ thuật số